Pengembangan Instrumen Asesmen Autentik Ranah Afektif pada Pembelajaran dalam Jaringan (Daring) di Kelas 4 Sekolah Dasar - Tia Tia; Wahyu Widodo; Moh. Farid Nurul Anwar (Faculty of Teacher Training and Education, Musamus University, 2022)
Today's students and teachers face obstacles with online learning. Teachers struggle to evaluate the learning results of their students, and the students themselves cannot find authentic tasks. The purpose of this research and development is to develop products, namely effective assessment instruments in the affective realm of online learning using the Borg & Gall model, that meet valid and effective requirements. The results obtained in the development are in two aspects, namely validity and effectiveness. The results of the validation itself obtained results, namely, instrument experts obtained 75% and linguists obtained 80%. Both of these validation results show that the product can be used. Furthermore, on the effectiveness of the product, namely by questionnaires of teacher and student responses. In the questionnaire, students' responses obtained a result of 80.6%, while the teacher's questionnaire obtained a result of 90%. The results of this effectiveness test show that the product of the authentic assessment instrument is feasible, effective, and can be implemented. It can be concluded that this valid and effective authentic assessment instrument product can be a solution to the problem of assessment or assessment in the affective realm at SDN Merjosari 2 Malang City during online learning.